Electrical stimulation with periodic alternating intervals stimulates neuronal cells to produce neurotrophins and cytokines through activation of mitogen‐activated protein kinase pathways. (29th October 2015) - Yamamoto, Kenta; Yamamoto, Toshiro; Honjo, Kenichi; Ichioka, Hiroaki; Oseko, Fumishige; Kishida, Tsunao; Mazda, Osam; Kanamura, Narisato
Abstract : Peripheral neuropathy is a representative complication of dental surgery. Electrical therapy, based on electrical stimulation with periodic alternating intervals (ES‐PAI), may promote nerve regeneration after peripheral nerve injury in a non‐invasive manner, potentially providing an effective therapy for neuropathy. This study aimed to analyze the molecular mechanisms underlying the nerve recovery stimulated by ES‐PAI. In brief, ES‐PAI was applied to a neuronal cell line, Neuro2A, at various intensities using the pulse generator apparatus, FREUDE. Cell viability, neurotrophin mRNA expression, and cytokine production were examined using a tetrazolium‐based assay, real‐time RT‐PCR, and ELISA, respectively. Mitogen‐activated protein kinase (MAPK) signaling was assessed using flow cytometry. It was found that ES‐PAI increased the viability of cells and elevated expression of nerve growth factor (NGF) and neurotrophin‐3 (NT‐3); ESPAI also augmented vascular endothelial growth factor (VEGF) and platelet‐derived growth factor (PDGF) expression, which was restored by addition of p38 inhibitors. Phosphorylation of p38 and extracellular signal‐regulated kinase 1/2 (ERK‐1/2) was augmented by ES‐PAI. Hence, ES‐PAI may ameliorate peripheral neuropathy by promoting neuronal cell proliferation and production of neurogenic factors by activating p38 and ERK‐1/2 pathways.